Determination of Power Losses in Solar Panels Using Artificial Neural Network - Jazayeri, Kian (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: The world’s traditional energy resources remain insufficient with respect to the increasing energy requirements of the modern era. In recent decades the threats and limitations associated with energy resources such as fossil fuels have motivated researches to find alternative clean and sustainable energy resources. Concentrated solar power is considered as one of the most competitive and rapidly growing renewable energy resources which emerge to meet the modern world’s increasing energy requirements. Along with the rising demand for alternative energy resources, the technologies and methods regarding utilization of solar energy have been the subject of many scientific works recently. Solar panels made of solar cells generate electrical power from sun’s radiations and developing management and controlling techniques for solar panels plays a major role in benefitting from solar energy. The purpose of this study is to develop an intelligent fault detection system which provides possibilities of real time monitoring and fault detection of solar panels. Utilizing artificial neural network technology, the intelligent solar panel fault detection system is capable of perceiving sun’s position in the sky and estimating the corresponding output power of a solar panel based on algorithms derived by the artificial neural network which has been trained on solar data at several time intervals. The system being capable of operating in any geographical location provides possibilities of 24-hour monitoring and fault detection as well as future power estimations for solar panels. Keywords: Renewable Energy, Photovoltaic, Solar Energy, Solar Panel/Cell, Intelligent Fault Detection, Artificial Neural Network, Output Power Estimation. ………………………………………………………………………………………………………… ÖZ:Modern asrın artan enerji ihtiyaçları dikkate alındığında dünyanın geleneksel enerji kaynaklarının yetersiz kaldığı görülmektedir. Son yıllarda özellikle fosil yakıtlar ve buna benzer enerji kaynaklarına yönelik olan sınırlamalar ve tehditler, araştırmaların alternatif temiz ve sürdürülebilir enerji kaynakları üzerinde yoğunlaşmasına neden olmuştur. Yoğunlaştırılmuş güneş enerjisi, modern dünyanın artan enerji ihtiyaçlarını karşılamak üzere alternatif olarak düşünülen, rekabet gücü en yüksek olan ve hızlı bir şekilde büyüyen yenilenebilir bir enerji kaynağı konumundadır. Alternatif enerji kaynaklarına yönelik olan taleplerin artması ile birlikte, güneş enerjisinin kullanımı ile ilgili olan teknoloji ve yöntemler de birçok bilimsel çalışmaya konu olmuştur. Güneş hücrelerinden oluşan güneş panelleri, güneş ışınlarından elektrik enerjisi üretmekte olup bu panellere yönelik gelişme yönetimi ve kontrol teknikleri güneş enerjisinden yararlanma yönünde önemli bir rol oynamaktadır. Bu çalışmada güneş panelleri için gerçek zamanlı izleme ve hata belirleme olanaklarını sağlayan akıllı bir hata belirleme sisteminin geliştirilmesi amaçlanmaktadır. Yapay zeka ağları teknolojisinden yararlanılarak güneş panelleri için tasarlanan akıllı hata blirleme sistemi, güneşin gökyüzündeki konumunu algılama ve çeşitli zaman aralıklarında toplanan solar bilgiler ile eğitilmiş olan yapay zeka ağları tarafından elde edilen algoritmalara dayanarak ilgili çıkış güçlerini tahmin etme kabiliyetine sahip olmaktadır. Herhangi bir coğrafi konumda çalışma kabiliyetine sahip olan sistem, güneş panellerine yönelik 24 saat izleme ve hata belirleme olanaklarının yanısıra güç tahmin olanaklarını da sağlamaktadır. Anahtar Kelimeler : Yenilenebilir Enerji, Güneş Enerjisi, Güneş Paneli/Hücresi, Akıllı Hata Belirleme, Yapay Zeka Ağları, Güç Tahmini.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2012. Supervisor: Prof. Dr. Şener Uysal.
Keywords: Electrical and Electronic Engineering; Electric Power Production - Solar Energy; Renewable Energy - Photovoltaic - Solar Panel/Cell; Intelligent Fault Detection - Artificial Neural Network - Output Power Estimation